Interface-mediated hygroelectric generator with an output voltage approaching 1.5 volts - Huang, Yaxin; Cheng, Huhu; Yang, Ce; Zhang, Panpan; Liao, Qihua; Yao, Houze; Shi, Gaoquan; Qu, Liangti (Nature communications, 2018)
Hygroelectricity is proposed as a means to produce electric power from air by absorbing gaseous or vaporous water molecules, which are ubiquitous in the atmosphere. Here, using a synergy between a hygroscopic bulk graphene oxide with a heterogeneous structure and interface mediation between electrodes/materials with Schottky junctions, we develop a high-performance hygroelectric generator unit with an output voltage approaching 1.5 V. High voltage (e.g., 18 V with 15 units) can be easily reached by simply scaling up the number of hygroelectric generator units in series, enough to drive commercial electronic devices. This work provides insight for the design and development of hygroelectric generators that may promote the efficient conversion of potential energy in the environmental atmosphere to electricity for practical applications. Hygroelectric generators comprised of electrodes and a hygroscopic material with a chemical-gradient structure can produce electricity by absorbing water vapor. Here, the authors achieve a high output voltage by employing hygroscopic heterogeneous graphene oxide and materials with Schottky junctions.